Overexpression of SET and MYND Domain-Containing Protein 2 (SMYD2) Is Associated with Tumor Progression and Poor Prognosis in Patients with Papillary Thyroid Carcinoma - Xu, Wenchao (Med Sci Monit, 2018)
BACKGROUNDS: SET and MYND domain-containing protein 2 (SMYD2), which is identified as a protein-lysine methyltransferase, plays a crucial role in the progression of some tumors such as bladder carcinoma. However, the clinical significance of SMYD2 in patients with papillary thyroid carcinoma (PTC) has not been elucidated. In the present study, we aimed to investigate the expression and role of SMYD2 in human PTC. MATERIAL/METHODS: Clinicopathological analysis was performed in 107 patients with PTC. Expression of SMYD2 was determined by immunohistochemistry staining, quantitative RT-PCR, or Western blotting in PTC tissues, adjacent normal tissues, and PTC cells (K1 and B-CPAP). The prognostic value of SMYD2 in PTC patients was assessed by univariate and multivariate analysis. Clinical outcomes were evaluated by Kaplan-Meier log-rank tests. Cell proliferation was examined in PTC cells following overexpression or knockdown of SMYD2. RESULTS: SMYD2 was highly expressed in PTC tissues compared to adjacent thyroid tissues. Additionally, high expression of SMYD2 was significantly related to tumor size, lymph node metastasis, and TNM stage. Moreover, SMYD2 was identified as an independent prognosis factor by multivariate analysis. Using 2 PTC cell lines, K1 and B-CPAP, we demonstrated that high expression of SMYD2 can promote tumor cell proliferation. CONCLUSIONS: SMYD2 expression was upregulated in PTC tissues and significantly related to the poorer prognosis of PTC patients. Our studies suggested the potential role of SMYD2 as a new therapeutic target and prognostic biomarker in human PTC.